Adopting Incremental Innovation Approaches in the Digitalization of Village Government Services - Jamaluddin Ahmad (Magister Ilmu Administrasi Publik, 2020)
Although much research has established the importance of digitalization in public services, in practice, village governments responsible for village community services often obscure public perceptions about the potential impact on digital-based public services. This study aims to provide a more detailed picture of the incremental innovation approach in the implementation of public services, especially the adoption of digital technology in the delivery of village government service. This research is a case study research that uses a qualitative research design. study results underline the importance of the incremental innovation approach. Digitalization impacts public perceptions about transparency, speed, and accountability; willingness to accept changes, especially changes in the use of mobile phones (mobile phones) as needed; and resultant social impact. Thus, study results are an invaluable input into the decision-making process related to public services.